2018
DOI: 10.1007/s40556-017-0145-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation in Complicated Monochorionic Pregnancy: Initial Experience

Abstract: To evaluate outcomes of complicated monochorionic pregnancies intervened by radiofrequency ablation (RFA) and report the initial experience. It is a retrospective case series of 15 cases of complicated monochorionic twin pregnancies intervened by RFA in Mediscan Systems Chennai, a tertiary referral Fetal Medicine center, from February 2015 till February 2017. Perinatal outcomes were available for all 15 cases. Main indication for RFA was sIUGR in 10 cases, of which 2 had coexistent Twin to Twin Transfusion syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Van Den Bos et al (6) reported an overall PPROM rate of 19.8% with 43.5% babies born between 28 and 37 weeks’ gestation. Bebbington et al (8) reported an overall PPROM rate of 21.9% after RFA and BCC with preterm delivery (<34 weeks) in 59% of RFA and 44% of BCC procedures (11). In our series, 30% women delivered before 32 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Den Bos et al (6) reported an overall PPROM rate of 19.8% with 43.5% babies born between 28 and 37 weeks’ gestation. Bebbington et al (8) reported an overall PPROM rate of 21.9% after RFA and BCC with preterm delivery (<34 weeks) in 59% of RFA and 44% of BCC procedures (11). In our series, 30% women delivered before 32 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably one of the few studies from developing countries to deal with selective fetal reduction in complicated monochorionic twin pregnancies. The only other studies from our country include a retrospective series of 15 cases of complicated monochorionic twin pregnancies managed by RFA (11) and a single case of complicated TRAP sequence managed by interstitial laser (12).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably one of the few studies from developing countries to deal with selective fetal reduction in complicated monochorionic twin pregnancies. The only other studies from our country include a retrospective series of 15 cases of complicated monochorionic twin pregnancies managed by RFA [11] and a single case of complicated TRAP sequence managed by interstitial laser [12]. Even though we performed the procedure in a small number of patients, this study highlights the feasibility of selective fetal reduction in complicated monochorionic twins in a low-resource setting.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 94%